Kingdom of the Netherlands-Aruba : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This Background Paper describes economic and financial developments in Aruba during 1997-98. The paper highlights that in the mid-1990s, the boom in the hotel sector came to an end, and the economy started to grow at a more sustainable pace. The paper reviews real economic activity, employment, and domestic price movements. It covers public finances and fiscal policy, including the budget for 1999, and also addresses monetary and exchange policy and developments. An analysis of recent trends in the external current and capital accounts is also presented.